2016
DOI: 10.7150/thno.12350
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic Approach Identifies KRAS as a Positive Regulator of CREG1 in Non-small Cell Lung Cancer Cells

Abstract: Protein glycosylation plays a fundamental role in a multitude of biological processes, and the associated aberrant expression of glycoproteins in cancer has made them attractive biomarkers and therapeutic targets. In this study, we examined differentially expressed glycoproteins in cell lines derived from three different states of lung tumorigenesis: an immortalized bronchial epithelial cell (HBE) line, a non-small cell lung cancer (NSCLC) cell line harboring a Kirsten rat sarcoma viral oncogene homolog (KRAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Six human lung adenocarcinoma cell lines, A549, H358, H441, HCC827, H1650 and H1975 cells, were purchased from the American Type Culture Collection (ATCC). A549 (G12S), H358 (G12C) and H441 (G12V) harbor the KRAS mutation . HCC827 (E746‐A750 deletion), H1650 (E746‐A750 deletion) and H1975 (L858R and T790M) harbor the EGFR mutation .…”
Section: Methodsmentioning
confidence: 99%
“…Six human lung adenocarcinoma cell lines, A549, H358, H441, HCC827, H1650 and H1975 cells, were purchased from the American Type Culture Collection (ATCC). A549 (G12S), H358 (G12C) and H441 (G12V) harbor the KRAS mutation . HCC827 (E746‐A750 deletion), H1650 (E746‐A750 deletion) and H1975 (L858R and T790M) harbor the EGFR mutation .…”
Section: Methodsmentioning
confidence: 99%
“…siRNA-mediated knockdown of CREG inhibited cancer cell proliferation. In a SILAC (stable isotope labeling with amino acids in cell culture) proteomic study of non-small cell lung cancer cell lines, Clark et al (2016) found that CREG was highly expressed and closely correlated with K-Ras mutations in lung cancer cells. siRNA knockdown of K-Ras suppressed CREG expression, while depletion of CREG in the K-Ras mutant lung cancer cell lines inhibited proliferation.…”
Section: The Biological Activity Of Cregmentioning
confidence: 99%
“…5 A) including two transcription factors CREG1 and MECOM between TCGA and GSE40791 (Pearson's correlation test, FDR <0.05, R > 0.3). CREG1 has a potential role in cell proliferation and migration in NSCLC cells [ 51 ]. MECOM is significantly amplified in lung adenocarcinoma [ 10 ].…”
Section: Resultsmentioning
confidence: 99%